Specyfika pracy oraz rola logopedy w interdyscyplinarnym modelu opieki nad chorym po udarze mózgu - Osowicka-Kondratowicz, Magdalena; Białkowska, Joanna; Białkowski, Paweł (Papers in Linguistics, 2019)
The interdisciplinary team involved in the rehabilitation process of the post-CVA patient requires close co-operation among all involved health care professionals in order to ensure a continuous exchange of information and to relate the same information to the patient. The lack of awareness of each team member’s work-related tasks could jeopardize the effectiveness of the rehabilitation process instead of enhancing it. Therapeutic goals cannot be achieved during the rehabilitation process if there is inadequate team cooperation when treating a patient. For example, unfamiliarity with the treatment approach that is utilized by the speech therapist may cause developing pathological movement patterns in CVA patients. Interdisciplinary teamwork is a complex process which needs to be based on exchanging knowledge and skills to impact patient care. The purpose of this article is to describe the speech therapy approach to the rehabilitation of a post CVA patient. This type of approach needs to be included in the planning of a complex care for a population of patients with neurological disorders, especially for those suffering from CVA. These patients comprise the majority of neurological disorders.